2020
DOI: 10.1007/s00420-020-01581-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adverse social behaviour at the workplace on subsequent mental distress: a 3-year prospective study of the general working population in Norway

Abstract: Objective We aimed to provide an integrated picture of the relationship between different facets of adverse social behaviour (ASB) at work and mental health problem. Methods Data were provided from a longitudinal nationwide study of the general population in Norway. Eligible respondents were in paid work during a reference week in 2013, or temporarily absent from such work, and was interviewed at 3-year follow-up (n = 3654, response at baseline/follow-up = 53.1%/71.8%). We investigated the prospective assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…23-25 28 Three of these did not specify if the harasser was a co-worker or someone else (eg, a client). [23][24][25] Their results relate most closely to our compound measure of workplace sexual harassment. All three studies found pronounced associations of sexual harassment with prospective mental ill health.…”
Section: Comparison To Prior Studies and Interpretationmentioning
confidence: 59%
See 2 more Smart Citations
“…23-25 28 Three of these did not specify if the harasser was a co-worker or someone else (eg, a client). [23][24][25] Their results relate most closely to our compound measure of workplace sexual harassment. All three studies found pronounced associations of sexual harassment with prospective mental ill health.…”
Section: Comparison To Prior Studies and Interpretationmentioning
confidence: 59%
“…9 15 22 To the best of our knowledge, all prospective studies that have investigated the association of sexual harassment with self-reported mental health outcomes found associations in women, while in men, the results have been less consistent. [23][24][25] In the only prospective study using register data on mental ill health (based on the same survey items for sexual harassment as this study), an increased risk of suicide attempts and suicides in victims of work-related sexual harassment was found. 26 To our knowledge, the prospective relationship between work-related gender harassment and mental ill health has not previously been investigated, and no study so far has explored the prospective association of sexual or gender harassment with the use of psychotropic medication.…”
Section: Workplacementioning
confidence: 64%
See 1 more Smart Citation
“…Effects of ASBs on mental distress has been reported in a sister paper. 25 Threats/acts of violence was measured with three items: 'Over the past 12 months have you (Q1) been the victim of violence at the workplace that caused visible marks or physical damage? (Q2) been the victim of violence at the workplace that did not cause visible marks?…”
Section: Measurement Of Asbsmentioning
confidence: 99%
“…Moreover, these studies are essentially based on self-reported data from questionnaires 2,8,13) or telephone interviews 14) , which may lead to information, recall and report bias, or non-differential misclassification.…”
Section: Introductionmentioning
confidence: 99%